Helping Countries Develop : The Role of Fiscal Policy - Clements, Benedict (International Monetary Fund, 2004)
Fiscal policy can foster growth and human development through a number of different channels. These include the macroeconomic (for example, through the influence of the budget deficit on growth) as well as the microeconomic (through its influence on the efficiency of resource use). But how precisely do these channels work in developing countries? What kinds of tax and expenditure policies should developing countries implement to help them meet the Millennium Development Goals? And how can international aid be made more effective? Drawing on both theory and country experience, this book brings together IMF research on the various ways fiscal policy can be used to help spur economic development.